Patient-Reported Abdominal Morbidity Following Abdomen-Based Breast Reconstruction - Maus, Jacob; Pestana, Ivo A. (Journal of Reconstructive Microsurgery, 2023)
Background Abdominal wall morbidity occurs with increased frequency following flap harvest in the obese abdomen. Its impact on patient-reported outcomes (PROs) in breast reconstruction has been poorly characterized.Methods A retrospective review of obese patients undergoing abdominal-based free autologous breast reconstruction was conducted over 15 years. Patient operative characteristics were recorded and outcomes were analyzed. PROs were assessed using the BREAST-Q abdominal survey.Results In total, 75 women (108 flaps) with the mean body mass index (BMI) of 33.2 were included. Flaps included deep inferior epigastric artery perforator (24%), muscle-sparing (43%), and free transverse rectus abdominis myocutaneous flaps (f-TRAM; 33%). World Health Organization (WHO) obesity class, BMI, and flap type did not affect flap failure (1%) or complication rates. Hernia developed in 7%; all necessitated repair. Eight percent developed abdominal bulge; one was repaired. Hernia formation was associated with increased patient age (p < 0.05). Bulge formation occurred more often in f-TRAM donor sites (p = 0.005). BMI, WHO class, flap type, and mesh use were not related to hernia or bulge occurrence in either univariate or multivariate analysis. The survey response rate was 63%. Abdominal Physical Well-Being (proxy for abdominal wall function) and Satisfaction with Abdomen (patient-perceived cosmesis) were similar across flap types, age, and WHO classification groups. Patients with postoperative bulge reported higher abdominal physical well-being scores, regardless of flap type (p < 0.01). Bulge was correlated with lower satisfaction (p < 0.05).Conclusion The incidence of abdominal wall morbidity following abdominal free-tissue transfer for breast reconstruction was acceptably low in our population of obese patients. Hernia was a clinically significant complication, warranting surgical repair. Bulge was primarily a cosmetic concern and did not detract from patient-reported abdominal wall function. Age may represent an independent risk factor for hernia formation in this population.
Keywords: breast reconstruction; obesity; autologous breast reconstruction; abdominal donor site morbidity; PRO; bulge; hernia; DIEP flap; TRAM